Multi-Channel PWM Heater Control Chip in 0.18 μm High-Voltage CMOS for a Quantum Simulator - Christoph Ribisch; Michael Hofbauer; Kerstin Schneider-Hornstein; Alexander Kuttner; Martin Jungwirth; Horst Zimmermann (IEEE Photonics Journal)
A circuit to control heating resistors with a pulse-width modulated (PWM) signal for a photonic quantum simulator is introduced. The output voltage is switched on for a changeable specified time and switched off for the rest of the period. The length of the resulting current and voltage pulse determines the mean heating power on the resistors connected to the outputs. The PWM generation is delay-line based and fully scalable. The PWM signal has a voltage swing of 9.9 V to power the heating resistors and is also synchronized with an input clock. The chip is designed for an PWM base clock in the range of 100 MHz. The chip also includes transimpedance amplifiers (TIAs) to monitor light powers inside the photonic integrated circuit (PIC) of the quantum simulator. 40 PWM channels and eight TIA channels are monolithically implemented in an application-specific integrated circuit (ASIC) using a 0.18 μm high-voltage CMOS technology. The pulse duration for each channel can be set via a serial peripheral interface (SPI).